Students' Perceptions in Developing Authentic Assessment with Website Integrated to Measure Physics Learning Outcomes: A Need Analysis - Ihsan Nurrahman, Ahlun; Sukarmin, Sukarmin; Suharno, Suharno (KnE Social Sciences, 2024)
Assessment is one of the crucial roles in measuring student abilities to face challenges of the 21st century. This study examines how college students’ ambitions influence their perceptions and desires for authentic assessment, based on website development. Data series via interviews and closed query questionnaires were given to 131 high school students within the metropolis of Surakarta. Facts analysis used a qualitative method with descriptive strategies. The findings of this look suggest that 64% of 130 senior high school students find it tough to clear up physics questions. Students experience that they consider physics issues harder to resolve than the equations that have been memorized. Students want within the evaluation, they have experienced those actual troubles within the learning system so that the ability to understand principles, abilities, and attitudes can be higher. Therefore, it is far essential to expand real assessment as an incorporated device between getting to know and evaluation of getting to know to degree physics learning outcomes. Keywords: authentic assessment, website integrated, physics learning outcomes